Percutaneous transhepatic recanalization of occluded prosthetic graft after pancreatoduodenectomy with venous reconstruction for pancreatic cancer - Degrauwe, Nils; Roulin, Didier; Dunet, Vincent; Halkic, Nermin; Demartines, Nicolas; Digklia, Antonia; Villard, Nicolas; Denys, Alban; Tsoumakidou, Georgia; Duran, Rafael (Frontiers in Oncology, 2025)
IntroductionTo investigate the feasibility, safety, and efficacy of percutaneous transhepatic endovascular recanalization and stenting after venous graft thrombosis in pancreatic cancer patients who underwent pancreatoduodenectomy (PD) with venous reconstruction and assess risk factors of occlusion.MethodsThis retrospective study was approved by the institutional review board. The clinical characteristics of 227 patients who underwent PD were compared among patients who underwent PD with/without porto-mesenteric venous resection (PMVR) ± prosthetic graft interposition.ResultsOut of 227 patients, 18 (8%) underwent PD with PMVR and prosthetic graft interposition. Seven out of 18 patients had prosthetic graft occlusion. Occlusion was symptomatic in most cases (86%) and associated with tumor recurrence in 43%. On univariable logistic regression analysis, small postoperative graft diameter (OR: 0.141; 95% CI 0.021–0.970) and caudal anastomosis diameter measured on CT (OR: 0.226; 95% CI 0.059–0.859) were clear predictors of graft occlusion (p = 0.047 and p = 0.029, respectively). Interventional recanalization was performed in five patients. Technical success was 100%, with no complications.DiscussionPercutaneous transhepatic prosthetic graft recanalization and stenting is feasible and may be considered a safe and effective technique with immediate restoration of porto-mesenteric blood flow and symptom relief. Small grafts and venous anastomosis diameters are particularly at risk of thrombosis.